Clinical researchPostprandial metabolic heterogeneity in men with primary dyslipidaemia - Pavlidis, Antonios N.; Kolovou, Genovefa D.; Anagnostopoulou, Katherine K.; Petrou, Petros C.; Cokkinos, Dennis V. (Archives of Medical Science, 2010)
Introduction : Familial combined hyperlipidaemia (FCH) and familial hypercholesterolaemia (FH) have been strongly linked to premature coronary artery disease. Postprandial hypertriglyceridaemia is also associated with atherosclerotic disease. We evaluated the postprandial lipaemia in men with FCH and FH and compared them to a group of healthy men. Material and methods : The study population consisted of 83 men: 34 FCH, 29 FH and 20 healthy. The FCH and FH groups were further divided into five subgroups, according to their lipid phenotype: FCH-IIA (n = 13), FCH-IIB (n = 10), FCH-IV (n = 11), FH-IIA (n = 21) and FH-IIB (n = 8). Postprandial lipaemia was evaluated by the areas under the curve for triglyceride (TG) concentrations (TG-AUC). Results : The TG levels after oral fat tolerance test were significantly higher in FCH, compared to FH and healthy groups (TG-AUC in mg/dl/h; 2678 ±1415 vs. 1503 ±1147 and 1011 ±652 respectively, p < 0.001). The postprandial response was higher in FCH-IV and FCH-IIB, compared to FCH-IIA (TG-AUC in mg/dl/h; 3220 ±824 or 3409 ±770 vs. 1863 ±577 respectively, p < 0.001, for both comparisons). The FCH-IIA group showed higher postprandial TG levels when compared to FH-IIA (TG-AUC in mg/dl/h; 1863 ±577 vs. 1374 ±428 respectively, p = 0.008). There were no significant differences between FH-IIB and FCH-IIB subgroups. There was a significant correlation (r = 0.907, p < 0.001) between the postprandial TG-AUC and fasting TG levels in all FCH subjects. Conclusions : All phenotypes of FCH and the FH IIB phenotype demonstrate an exaggerated postprandial response that could partially contribute to the high cardiovascular risk. These patients should be identified and treated early with the appropriate hypolipidaemic agents.